Pengaruh Kualitas Pelayanan, Keterikatan Emosional, dan Religiusitas Terhadap Kepuasan Nasabah dan Loyalitas Nasabah: Survei Pada Nasabah Bank BJB Syari’ah Jawa Barat, Banten Dan DKI Jakarta - Aceng Kurniawan; Saldi Rizki Nugraha (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of service quality, emotional attachment, and religiosity on customer satisfaction and loyalty of Bank BJB Syariah customers in West Java, Banten, and DKI Jakarta. The method used was a quantitative survey with data collected via Google Forms and purposive – quota sampling, involving 240 respondents. Data analysis using IBM SPSS Version 20 showed that service quality and emotional attachment significantly affect customer satisfaction, while religiosity does not have a significant effect. Furthermore, service quality, emotional attachment, and religiosity significantly influence customer loyalty. Customer satisfaction also has a significant effect on loyalty. Mediation testing using the Sobel calculator revealed that customer satisfaction mediates the effect of service quality and emotional attachment on loyalty but does not mediate the effect of religiosity on loyalty. These findings emphasize the importance of improving service quality and emotional attachment to maintain customer satisfaction and loyalty. Although religiosity does not have a direct or mediated effect through satisfaction, segmenting customers based on religiosity levels remains important for Bank BJB Syariah’s marketing strategy